Prevalence of Depression among the Farmers and its Determinants: A Cross Sectional Study - Mohamed Tanveer Ahmed; Jyothi Jadhav; Vishwanatha (Medsci Publications, 2019)
Context: India being an agrarian country, where agriculture plays a vital role in ensuring food security and poverty alleviation. Farmers who are completely involved in agriculture face a number of unique occupational stressors such as physical environment, family structure, farm economy. These stressors have resulted in various psychiatric disorders such as depression, anxiety resulting in high rates of suicides among farmers. Aim: To assess the prevalence of depression among farmers and its determinants in selected villages of Bangalore rural district. Materials and Methods: A cross sectional study was conducted among 570 farmers in 12 selected villages of Nelamangala in Bangalore rural district. The level of depression was assessed using Centre for Epidemiological studies- Depression scale. Data analysis was done using descriptive statistics and chi-square. Results: The overall prevalence of depression was found to be 33.9% among the farmers. About 46.5% of study subjects were not literates and majority (47.9%) were from lower middle class. Conclusion: The prevalence of depression was found to be high among farmers compared to the general population. Various factors like loan from multiple sources with high interest, have implicated in high incidence of depression. Hence measures should be planned to help the farming community to overcome this psycho-social distress and to lead a productive life.